کرشن چندر کا افسانہ " کچرا بابا" کے منفی کردار - Suliman, Muhammad; Bhukari, Badshah Munir (Khayaban - خیابان, 2021)
Abstract: If there is a name is a progressive shot story writer who achieved brilliance and fame after Prem Chand it was not other than Krishan Chandar. One can quench his thirst for subject; krishan chandar has dealt with, in his stories. Adding to this he is knowledgeable about and has a considerable command on the themes he chooses. There would barely be any aspect of life that would have been slipped away from his observations and experiences. There are various subjects scattered in his stories like starvation, poverty, sexuality, psychology, love and beauty, class conflict of the individuals of the lover, upper and middle classes, social and economic crisis, politics, religion and sectarianism.